An Integrated Gut Microbiota and Network Pharmacology Study on Fuzi-Lizhong Pill for Treating Diarrhea-Predominant Irritable Bowel Syndrome - Zhen, Zhang; Xia, Lin; You, Huang; Jingwei, Zhou; Shasha, Yang; Xinyi, Wei; Wenjing, Lai; Xin, Zhang; Chaomei, Fu (Frontiers in Pharmacology, 2021)
Abstract: Diarrhea-predominant irritable bowel syndrome (IBS-D) is one of the most common chronic functional gastrointestinal diseases with limited treatments. Gut microbiotas play an important role in chronic gastrointestinal diseases. In traditional Chinese medicine (TCM), Spleen-Yang deficiency (SYD) is one of the root causes of IBS-D. Fuzi-lizhong pill (FLZP) is well-known for its powerful capacity for treating SYD and has a good clinical effect on IBS-D. However, the mechanism of FZLP on the gut microbiotas of IBS-D has not been fully clarified. Our present study aimed to reveal the mechanism of FLZP regulating gut microbiota of IBS-D. The body mass, CCK, MTL and Bristol fecal character score were used to verify the establishment of IBS-D model. IL-6, TNF, IL-1β and IFN-γ were crucial targets screened by network pharmacology and verified by Elisa analysis. Eighteen gut microbiotas were important for the treatment of IBS-D with FLZP. Bacteroidetes, Blautia, Turicibacter and Ruminococcus_torques_group were the crucial gut microbiotas that FLZP inhibits persistent systemic inflammation in IBS-D model. Lactobacillus is the crucial gut microbiota that FLZP renovates intestinal immune barrier in IBS-D model. In summary, FLZP can affect bacterial diversity and community structures in host and regulate inflammation and immune system to treat IBS-D.